2018
DOI: 10.1177/1468087418783118
|View full text |Cite
|
Sign up to set email alerts
|

Reverse breathing in diesel engines for aftertreatment thermal management

Abstract: Approximately 40% of typical heavy-duty vehicle operation occurs at loaded idle during which time conventional diesel engines are unable to maintain aftertreatment component temperatures in a fuel-efficient manner. Fuel economy and thermal management at this condition can be improved via reverse breathing, a novel method in which exhaust gases are recirculated, as needed, from exhaust to intake manifold via one or more cylinders. Resultant airflow reductions increase exhaust gas temperatures and decrease exhau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The contributing factors to brake thermal efficiency (BTE) are open cycle efficiency (OCE), closed cycle efficiency (CCE) and mechanical efficiency (ME). The three efficiencies contribute to the brake thermal efficiency (BTE) as shown in equation (11). Additional details can be found in Stanton.…”
Section: Efficiency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The contributing factors to brake thermal efficiency (BTE) are open cycle efficiency (OCE), closed cycle efficiency (CCE) and mechanical efficiency (ME). The three efficiencies contribute to the brake thermal efficiency (BTE) as shown in equation (11). Additional details can be found in Stanton.…”
Section: Efficiency Analysismentioning
confidence: 99%
“…Recent results from literature demonstrate that low-airflow strategies – including cylinder deactivation (CDA), 8 intake valve modulation, 9 cylinder cut-out, 10 and internal EGR via reverse-breathing and intake re-breathing 11 can be used to maintain desirable ATS temperatures in a fuel-efficient manner at idle. This is achieved by maintaining engine-outlet temperatures elevated enough to delay cool-down of a warmed-up ATS, while maintaining NO X emissions lower than the conventional thermal management operation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by several of the authors, and others, have demonstrated the ability to raise exhaust temperatures for more efficient aftertreatment thermal management (TM) by utilizing various strategies such as maximally closing a variable geometry turbine (VGT), cylinder deactivation (CDA), intake valve modulation, and exhaust valve modulation. 2,1017…”
Section: Introductionmentioning
confidence: 99%